2022
DOI: 10.1088/1755-1315/1005/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Improving coffee quality through yeast addition in the fermentation process to support sustainable coffee production

Abstract: Indonesia is the fourth largest country in the world as a coffee producer. Coffee has complex chemical structure with volatile and non-volatile compounds, this composition has an important role in the distinctive coffee’s taste. Fermentation is an important stage in coffee processing, it has a direct effect on the coffee’s quality. So far, many people have done traditional fermentation relying on natural microbes in fresh coffee. The purpose of this study was to improve coffee’s quality by controlled fermentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…This study is in line with that conducted by [18] which states that aerobic fermentation can produce temperatures reaching 40-45℃. This study is also in line with [19], which states that the temperature in anaerobic fermentation ranges from 28-31℃. According to [20], the optimum temperature for yeast growth ranged from 20-30 °C so that the temperatures during anaerobic fermentation, anaerobic with H. uvarum and anaerobic with C. parapsilosis obtained were suitable as conditions for yeast growth.…”
Section: Temperature During Fermentation Processsupporting
confidence: 90%
See 1 more Smart Citation
“…This study is in line with that conducted by [18] which states that aerobic fermentation can produce temperatures reaching 40-45℃. This study is also in line with [19], which states that the temperature in anaerobic fermentation ranges from 28-31℃. According to [20], the optimum temperature for yeast growth ranged from 20-30 °C so that the temperatures during anaerobic fermentation, anaerobic with H. uvarum and anaerobic with C. parapsilosis obtained were suitable as conditions for yeast growth.…”
Section: Temperature During Fermentation Processsupporting
confidence: 90%
“…The analysis of variance carried out showed that the value of sig.> 0.05 so that it can be concluded that there was no significant difference between the fermentation treatment with TSS at the end of the fermentation. The results obtained are in line with research conducted by [19], which stated that the use of yeast had no significant effect on the total dissolved solids in the fermented water with an TSS value of approximately 2.5 at the end of fermentation.…”
Section: Figure 5 Tital Soluble Solid Of Fermented Juice Changes Duri...supporting
confidence: 90%
“…Controlling the fermentation temperature is necessary not only for the process development, but also to satisfy the demands of consumers regarding the improvement in coffee sensory profiles. In this sense, the main efforts with promising results have focused on achieving control of fermentation through the establishment of microbial starter cultures, the activity of which produces compounds that modify the chemistry of the coffee beans and highlight the attributes of the drink [11,16,27,61,[66][67][68]. Based on the results obtained in this research, temperature control is another mechanism by which the same effect can be achieved to determine the optimal conditions that can support the desired behaviors among native microbiota.…”
Section: Discussionmentioning
confidence: 87%
“…Various reports have successfully improved the flavor quality of Arabica coffee by using starters such as Wickerhamomyces anomalus KNU18Y3 and Wickerhamomyces anomalus YWP1-3 9 , 10 . Moreover, yeast starters such as Saccharomyces cerevisiae and Pichia kudriavzevii were applied for Robusta coffee ( Coffea robusta ) fermentation under controlled fermentation in a bioreactor 39 .…”
Section: Discussionmentioning
confidence: 99%